2016
DOI: 10.1016/j.ekir.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Enrichment Design in Clinical Trials for Autosomal Dominant Polycystic Kidney Disease: The TEMPO 3:4 Clinical Trial

Abstract: IntroductionPatients with slowly progressive autosomal dominant polycystic kidney disease (ADPKD) are unlikely to experience outcomes during randomized controlled trials (RCTs). An image classification of ADPKD into typical (diffuse cyst distribution) class 1A to E (by age- and height-adjusted total kidney volume [TKV]) and atypical (asymmetric cyst distribution) class 2 was proposed for prognostic enrichment design, recommending inclusion of only classes 1C to 1E in RCTs.MethodsA post hoc exploratory analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 29 publications
(44 reference statements)
2
43
0
Order By: Relevance
“…The MIC model depends on the assumption of exponential growth of the kidney volume at a rate of α (%/year) from an HtTKV 0 of 150 mL/m at age 0. The MIC prediction model selected patients at high risk for rapid disease progression and improved clinical designs [23]. The present study confirmed that MIC subgroups were significantly correlated with the disease severity (Table 1), eGFR slope (Table 2; Fig.…”
Section: Discussionsupporting
confidence: 79%
“…The MIC model depends on the assumption of exponential growth of the kidney volume at a rate of α (%/year) from an HtTKV 0 of 150 mL/m at age 0. The MIC prediction model selected patients at high risk for rapid disease progression and improved clinical designs [23]. The present study confirmed that MIC subgroups were significantly correlated with the disease severity (Table 1), eGFR slope (Table 2; Fig.…”
Section: Discussionsupporting
confidence: 79%
“…The Mayo imaging classification has been validated by an independent study 25 and shown to be informative in post hoc analyses of several clinical trials. 24,26 In most patients, the ellipsoid equation using coronal, sagittal, and transverse diameters (obtained by various imaging modalities) provides a fairly accurate estimation of TKV, image class, and eligibility for treatment. We prefer a computed tomography (CT) scan (including contrast enhancement in patients with eGFR.60 ml/min per 1.73 m 2 ) or MRI scan without contrast (in patients with reduced eGFR).…”
Section: Step 2 Confirm the Diagnosis Of Rapidly Progressive Diseasementioning
confidence: 99%
“…Two recent studies evaluating an enrichment strategy using the MIC have been published [ 31 , 32 ]. The first post hoc analysis was conducted in early disease in the HALT-PKD study, a randomized controlled trial that studied the effect of rigorous versus standard blood pressure control on rates of TKV increase and eGFR decline in ADPKD subjects ages 15–49 years with preserved renal function (eGFR > 60 mL/min/1.73 m 2 ) at inclusion [ 33 ].…”
Section: Discussionmentioning
confidence: 99%